Analysis of PM2.5 and PM10 Levels in the Area Around the Celukan Bawang Coal Fried Steam Power Plant (CFSPP) Using an Air Quality Detector - Laurensius Ivander Colorado; I Made Gunamantha (Jurnal Penelitian Pendidikan IPA, 2025)
The Celukan Bawang (CFSPP) in Buleleng, Bali, utilizes coal as its primary fuel source, potentially impacting surrounding air quality and public health. This study aimed to analyze the concentrations of fine and coarse particulate matter (PM₂․₅ and PM₁₀) and to assess their environmental and health implications based on temporal and meteorological variations. The research was conducted from September to October 2025 using a quantitative descriptive method. Air quality measurements were taken at three sampling locations SP1 (east), SP2 (west), and SP3 (south) using an Air Quality Detector equipped with an optical light-scattering sensor and GPS. Data were analyzed using Microsoft Excel and compared to Indonesia’s ambient air quality standards (Government Regulation No. 22 of 2021). The results showed that PM₂․₅ concentrations ranged from 12.5–22.3 µg/m³ and PM₁₀ from 8.0–11.0 µg/m³, all below national thresholds (55 µg/m³ for PM₂․₅; 75 µg/m³ for PM₁₀). However, according to WHO (2021), guidelines, the PM₂․₅ value at SP1 (22.3 µg/m³) exceeded the daily exposure limit (15 µg/m³), indicating potential long-term risks such as respiratory and cardiovascular diseases. Overall, the air quality around CFSPP remains within national safety limits, although continuous monitoring and emission control are recommended to safeguard community health in downwind areas.